Universal Bibliographic Control: Understanding the Mechanism of Interntional standard book Number ISBN - Kaku, David (My University, 2023)
The Internationl Standard Book Number ISBN is one of the veritable tools for Universal bibliographic control mechanisms. In this article the author explains how the the ISBN system works aacross cuntries and regions. The discussion narrowed down to Nigeria perspective. The author also looked at the details conponents of the ISBN tool.
Keywords: Universal Bibliographic Control; ISBN